MENINGKATKAN MINAT SISWA DALAM KEGIATAN EKSTRAKURIKULER VOCAL GROUP DI SMP NEGERI 2 XII KAYU TANAM - Maridun Maridun; Tulus Handra Kadir; Esy Maestro (FBS Universitas Negeri Padang, 2018)
ABSTRACT This study aimed to describe the vocal group as an extracurricular learning at SMP 2 KayuTanam.This study was a qualitative study using descriptive method. The object was the implementation of vocal group of extracurricular learning at SMP 2 KayuTanam. The primary data were attained through observation, and interview, and the secondary data were taken from library research. The result showed that the well-planned activity led to the good result. The good implementation of vocal group at SMP 2 KayuTanam can be gained because of the contributions of the coach who planned the extracurricular learning and school’s principles that supported and facilitated the needs during the extracurricular time.